Menjadikan Perempuan Papua Yang Berdaya (Study Analisa GESI Terhadap Perempuan Papua Sebagai Agen Perdamaian dan Kohesi Sosial) - Anil Dawan; Andina Mega Larasati (Pusat Studi Wanita, Univesitas Kristen Indonesia, 2022)
This article aims to describe the results of the GESI analysis. The method used is the GESI (Gender Equality and Social Inclusion) assessment. From the results of the GESI analysis it was found that the role of Papuan women in religious activities was quite high, both in routine religious meetings and involvement in planning religious activity programs and peace education. However, from 4 (four types of involvement) it was found that women's role was only in the